Consistency analysis of mechanical properties of elements produced by FDM additive manufacturing technology - Banjanin,Bojan (2018)
ABSTRACT Additive manufacturing (AM) technology refers to the process of producing 3D objects by adding material in successive layers. Fused deposition modeling (FDM) is one of the AM technologies where objects are built by adding layers of melted thermoplastic filament onto the printing surface. Mechanical properties of FDM printed part depend on many influencing factors such as material composition, extruding temperature, printing parameters and environment temperature.